Evaluation model of nuclear emergency rescue drill based on AHP weight analysis - RUAN Fang; SHEN Chao; CHENG Yuan; ZHU Jingxian; LUAN Fei; WANG Jianye (He jishu, 2022)
BackgroundNuclear emergency rescue drill evaluation is the main basis for testing and improving the emergency rescue ability of nuclear emergency team. To date, nuclear emergency evaluation has mainly focused on individual aspects such as emergency response capabilities, radiation monitoring, medical rescue and decontamination, etc. Little attention was paid to the complete evaluation index system and model.PurposeThis study aims to evaluate the effect of nuclear emergency rescue exercise in real time by establishing a fuzzy evaluation model of nuclear emergency rescue exercise based on analytic hierarchy process (AHP).MethodsAccording to the nuclear emergency rescue process, based on the nuclear emergency rescue team structure, task classification, drill effects and personnel safety requirements, the Delphi method was used to establish the nuclear emergency rescue drill evaluation index system. The fuzzy comprehensive evaluation method (FCE) based on the AHP method was employed to carry out weight allocation and construct a multi-level fuzzy comprehensive evaluation model. Finally, the M310 nuclear power plant (NPP) was taken as an example to verify the established evaluation model.ResultsThe evaluation results on M310 NPP effectively examine the response ability and the actual drill effect of the emergency rescue team, and reveal the problems and deficiencies during the drill.ConclusionsThe effectiveness of established evaluation model is verified in this study.